Knowledge translation on dementia: a cluster randomized trial to compare a blended learning approach with a "classical" advanced training in GP quality circles - Rieger Monika A; Lefering Rolf; Butzlaff Martin E; Vollmar Horst C (BMC, 2007)
Abstract Background Thus far important findings regarding the dementia syndrome have been implemented into patients' medical care only inadequately. A professional training accounting for both, general practitioners' (GP) needs and learning preferences as well as care-relevant aspects could be a major step towards improving medical care. In the WIDA-study, entitled "Knowledge translation on dementia in general practice" two different training concepts are developed, implemented and evaluated. Both concepts are building on an evidence-based, GP-related dementia guideline and communicate the guideline's essential insights. Methods/Design Both development and implementation emphasize a procedure that is well-accepted in practice and, thus, can achieve a high degree of external validity. This is particularly guaranteed through the preparation of training material and the fact that general practitioners' quality circles (QC) are addressed. The evaluation of the two training concepts is carried out by comparing two groups of GPs to which several quality circles have been randomly assigned. The primary outcome is the GPs' knowledge gain. Secondary outcomes are designed to indicate the training's potential effects on the GPs' practical actions. In the first training concept (study arm A) GPs participate in a structured case discussion prepared for by internet-based learning material ("blended-learning" approach). The second training concept (study arm B) relies on frontal medical training in the form of a slide presentation and follow-up discussion ("classical" approach). Discussion This paper presents the outline of a cluster-randomized trial which has been peer reviewed and support by a national funding organization - Federal Ministry of Education and Research (BMBF) - and is approved by an ethics commission. The data collection has started in August 2006 and the results will be published independently of the study's outcome. Trial Registration Current Controlled Trials [ISRCTN36550981]